AI Chatbots vs. Human Nurses: A Deep Dive into Patient Satisfaction in the Digital Health Era - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
AI Chatbots vs. Human Nurses: A Deep Dive into Patient Satisfaction in the Digital Health Era The healthcare landscape is undergoing a profound transfor...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care